2020
DOI: 10.3390/polym12010108
|View full text |Cite
|
Sign up to set email alerts
|

Novel Phosphorus-Nitrogen-Containing Ionic Liquid Modified Metal-Organic Framework as an Effective Flame Retardant for Epoxy Resin

Abstract: Metal-organic frameworks (MOFs) have shown great potential in flame retardant applications; however, strategies for fully exploiting the advantages of MOFs in order to further enhance the flame retardant performance are still in high demand. Herein, a novel MOF composite was designed through the generated cooperative role of MOF (NH2-MIL-101(Al)) and a phosphorus-nitrogen-containing ionic liquid ([DPP-NC3bim][PMO]). The ionic liquid (IL) was composed of imidazole cation modified with diphenylphosphinic group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…This hierarchical strategy simultaneously improved the fire safety of UP and its mechanical property. Similar strategy was also reported by encapsulating P and N containing ionic liquid (IL) into MOF (NH2-MIL-101(Al)) as novel FR for EP [ 83 ], which solved the poor dispersion and neutralizing the effect of directly adding IL into polymers. This IL-modified MOF combined the advantages of both materials and exhibited the 51% and 37.8% reduction in pHRR and SPR, respectively.…”
Section: Mof Applied In Fire Retardancy Researchmentioning
confidence: 77%
“…This hierarchical strategy simultaneously improved the fire safety of UP and its mechanical property. Similar strategy was also reported by encapsulating P and N containing ionic liquid (IL) into MOF (NH2-MIL-101(Al)) as novel FR for EP [ 83 ], which solved the poor dispersion and neutralizing the effect of directly adding IL into polymers. This IL-modified MOF combined the advantages of both materials and exhibited the 51% and 37.8% reduction in pHRR and SPR, respectively.…”
Section: Mof Applied In Fire Retardancy Researchmentioning
confidence: 77%
“…Moreover, the nanoscale metal ions/clusters in MOFs play an important role in improving the FR and smoke suppression performances. Up to now, several metal centers have been selected to research the MOF-derived FRs, such as Co, 7 9 Zn, 10 12 Zr, 13 15 Al, 16 , 17 Fe, 18 20 Cu, 21 , 22 Ni, 23 25 Sn, 26 and Mo. 27 Hu et al have found that 2D layered and 3D block MOFs combining common transition metals (such as Fe, Co, Zr, and Ni) and rigid organic complexes showed better flame retardancy with less dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Once these FRs enter the environment, they can easily attach to any airborne particle and can travel distances far from their emission or production sites. Hence, traces of such non-biodegradable FRs can be found in freshwater, food products, ecosystems, or can even be inhaled if they are present in the air [ 20 ]. On the other hand, biodegradable FRs are the one that can be degraded by microorganisms in the soil or water and result in mineralization.…”
Section: Introductionmentioning
confidence: 99%